Biosynthesis and Characterization of ZnO Nanoparticles with Beet Extract (Beta vulgaris L.) as Latent Fingerprint Identification - Sri Adelila Sari; Riri Virzan Putri Br. Siregar; Luthfi Qori Nabillah; Hanisah Hasibuan; Naji Arafat Mahat (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2024)
The uniqueness and permanence of patterns make fingerprints one of the most significant forensic tools for individual identification. The issue is that conventional fingerprint powders, frequently used today, pose serious health and environmental risks due to their use of toxic chemicals. This novel study utilizes sustainable and innovative techniques to investigate the effectiveness of beetroot fruit extract for latent fingerprint visualization. Zinc oxide (ZnO) nanopowders were synthesized using a green synthesis method, having beet fruit extract as an aqueous solvent. For applications on porous and non-porous surfaces, the fabricated ZnO was characterized using Fourier Transform Infrared (FT-IR) spectroscopy, Scanning Electron Microscopy (SEM), and Energy Dispersive X-ray (EDX) analysis up to October 2023. Thirty samples were provided to perform latent fingerprint analysis. The results show that ZnO nanopowders synthesized using beet fruit extract could provide safe, non-destructive, and efficient visualization of the latent fingerprints. Of the six fingerprint patterns examined, the most common was the Plain Whorls pattern, which represented 47% of prints identified. These results highlight beet fruit extract's natural potential and efficacy as a contrast agent for imaging latent fingerprints. This clean approach can provide a novel alternative for forensic biology, characterized by low toxicity, sustainability, and high efficacy, which can lead to a safe forensic practice.